A comparative study of effectiveness of diagnostic tests (r K39 strip, IFAT and bone marrow stained smear) for visceral leishmaniasis. - Al sady, Raad A.; Al faham, Mohammad A.; Sultan, Baqur A.; Al Tama, Mohammed J. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Iraq is an endemic area for visceral leishmaniasis (VK=L) (kala-azar) which is caused by the intracellular parasite leishmania donovani.